Turkish–German Transnational Social Space: Stitching Across Borders. Issue 3 (31st October 2014) - Bilecen, Başak; Çatır, Gül; Orhon, Aslı
Abstract This paper examines the social protection strategies of migrants living in Turkish–German transnational social space. Drawing on 20 interviews conducted with migrants in Germany and ten with their significant others in Turkey with a matched sample, we investigate 'stitching' strategy, that is, a process by which migrants in the host country continually attach themselves to the society back in their country of origin and, as a result, tap into protective resources in their interpersonal networks. We discuss the significance of high levels of transnationality displayed by our sample in protective resource flows and the ways in which inequalities are created and recreated from the respondents' perspectives. By examining transnationality as a marker of heterogeneity, our study contributes to the literature through an in‐depth analysis of a major strategy for social protection while analysing the meaning of reciprocal relationships. Copyright © 2014 John Wiley & Sons, Ltd.